Violência no namoro entre adolescentes do ensino médio de uma Região Metropolitana no Sudeste do Brasil: estudo de base escolar - Pinto, Isaura Barros Alves (2025)
Introduction: Dating violence (DV) refers to intimate partner violence occurring between individuals in a close relationship, encompassing physical, emotional, or sexual abuse (including stalking). It also includes abusive behaviors in non-marital intimate relationships, whether heterosexual or homosexual, during early dating stages. DV can occur in person or electronically (e.g., through harassing messages or non-consensual sharing of intimate images online). Harmful relationships may emerge early and persist throughout life, leading to physical, emotional, and psychological trauma with short-, medium-, and long-term consequences. Multiple factors beyond the couple’s relationship—such as personal history and social context—contribute to dating abuse. Objectives: This study aimed to (1) review scientific literature on adolescent dating violence and (2) estimate the prevalence of physical and sexual DV among high school students in the metropolitan region of Vitória, Espírito Santo, Brazil, while examining associations with sociodemographic characteristics, behavioral factors, and prior experiences of violence. Methods: A cross-sectional analytical study was conducted between March and December 2023, using stratified cluster sampling of students from public and private high schools who were in romantic relationships. Data were collected via structured REDCap questionnaires administered on tablets. Outcome variables included physical and sexual DV. Analyses included descriptive statistics, bivariate tests (Pearson’s Chi-square and Fisher’s exact tests), and multivariate logistic regression, with calculation of crude and adjusted Odds Ratios (aOR), 95% confidence intervals (CI), and significance levels (p ≤ 0.05) using Stata 17.0. Results: The narrative review synthesized existing knowledge on DV, highlighting its occurrence across diverse contexts and its association with multiple risk factors. Among 1,238 adolescents (aged 14–19), 5.7% (95% CI: 4.5–7.1) reported physical DV, with higher prevalence among males (7.0%) than females (5.2%). Significant associations were found with age (>16 years), substance use, and prior bullying exposure (p Conclusion: The study highlights the alarming prevalence of physical and sexual DV among adolescents, emphasizing the urgent need for interventions to address violence in young romantic relationships. Early victimization can negatively impact emotional, social, and psychological development, underscoring the importance of prevention strategies. < 0.05). For sexual DV, 7.8% (95% CI: 6.4–9.4) reported victimization, with higher prevalence among females (9.3%) and non-heterosexual adolescents. Significant correlates included sexual activity, substance use, and prior bullying/cyberbullying (p < 0.05)